2018
DOI: 10.3889/oamjms.2018.188
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme (ACE) D Allele as a Risk Factor for Increase Serum Interleukin-6 and Interleukin-8 in Psoriasis Patients

Abstract: BACKGROUND:Psoriasis is a chronic, recurrent inflammatory skin disease. It is characterised by autoimmune, environmental factors and complex genetic disorder.AIM:To explore the role of IL-6, IL-8, and ACE I/D polymorphism in the pathogenesis of Psoriasis and investigation of the relationship between ACE polymorphism and occurrence of psoriasis.PATIENTS AND METHODS:In this study, we took 73 psoriasis patients and 47 healthy patients as a control. These two groups subjected to analysis for ACE gene I/D polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…This suggests that the DD genotype and the D allele of the ACE I/D gene are associated with increased susceptibility for acne development and was as the same as the condition in various inflammatory disorders where this polymorphism was investigated, including Behcet's disease, vitiligo, and psoriasis …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the DD genotype and the D allele of the ACE I/D gene are associated with increased susceptibility for acne development and was as the same as the condition in various inflammatory disorders where this polymorphism was investigated, including Behcet's disease, vitiligo, and psoriasis …”
Section: Discussionmentioning
confidence: 99%
“…The association between ACE gene I/D polymorphism and different skin disorders had been previously investigated but it was not investigated in AV. So, we tried to reveal the hypothesized link between ACE gene I/D polymorphism, and AV risk among a sample of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies reported their research in Caucasian ethnicity [21-23, 25-30, 32-34] and four studies [9,20,24,31] in Asian ethnicity. Among Caucasian ethnicity, four studies [23,26,27,33] were conducted in Arab population, four studies [21,25,28,29] enrolled European population, while the remaining four studies [22,30,32,34] evaluated other populations (Pakistani, Iranian and Turkish populations).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…With regard to the controls source, nine studies [9, 20, 23-27, 31, 34] enrolled hospital-based patients, two studies [29,30] were population-based, and five studies [21,22,28,32,33] enrolled controls of unknown origin. In most of the considered studies, the ratio of patients affected by different psoriasis subtypes was not reported [9,20,21,24,31,32,34], while only 5 and 4 studies were conducted in groups of patients affected predominantly by psoriasis vulgaris [22,25,26,28,33] and psoriatic arthritis [23,27,29,30], respectively. In all studies the used genotyping method was polymerase chain reaction (PCR).…”
Section: Study Characteristicsmentioning
confidence: 99%